Determinants of Missed Nursing Care for Cardiac Patients in Iran: A Mixed-method Study - Fatemeh Amrolahi-Mishavan; Abdolhossein Emami-Sigaroudi; Fatemeh Jafaraghaee; Hooman Shahsavari; Saman Maroufizadeh; Mohammad Babaeipour-Divshali (Journal of Holistic Nursing and Midwifery)
Introduction: The cardiac care unit (CCU) is a stressful environment where nurses play a crucial role in providing critical care to cardiac patients. Consequently, missed nursing care in these units can have detrimental effects on patient outcomes. Objective: This study aims to develop a model for the determinants of missed nursing care in the CCUs of hospitals in Iran. Materials and Methods: This is a mixed-method study that was conducted in 2023 in two stages. In the first stage, an initial model of the determinants of missed nursing care in CCUs was developed by combining the results of previous studies. In the second stage (quantitative phase), six questionnaires were completed by 202 CCU nurses from a teaching hospital in Rasht, Iran. To measure the missed nursing care score, job profile, work-life conflict, clinical competence, cardiac room climate, and organizational management, which included the MISSCARE survey, the work-family conflict scale (WFCS), and the competency inventory for registered nurse (CIRN). Data were analyzed using Pearson’s correlation test, independent t-test, one-way ANOVA, and hierarchical multiple linear regression analysis. Results: As the total score for nurses’ clinical competence increased, the total score of missed nursing care significantly decreased (β=-0.010, 95%CI; -0.014%, -0.007%, P<0.001). Also, as work-life conflict scores increased, the total score of missed nursing care increased significantly (β=-0.162, 95% CI; -0.269 %, -0.055%, P=0.003). Overall, 41.6% of the variance in missed nursing care was explained by the variables in the regression model. Conclusion: Attention should be given to demographic and job-related characteristics, work-life conflicts, and clinical competencies of nurses to reduce missed nursing care in CCUs.